The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3813/aaa.918397
|View full text |Cite
|
Sign up to set email alerts
|

HearCom: Hearing in the Communication Society

Abstract: Agroup of 28 research partners joined the EU-funded project HearCom with the overall aim to improve hearing communication. One of the main achievements has been the provision of advanced hearing screening tests by telephone and Internet. Next to that it wasaimed to harmonize hearing diagnostic tests for European languages. Forthis the concept of an Auditory Profile wasdefined on which anumber of diagnostic hearing tests were developed in several languages. As hearing problems are also aresult of adverse acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 21 publications
(33 reference statements)
2
44
0
Order By: Relevance
“…This research was part of the European project HearCom (Hearing in the Communication Society, Vlaming et al, 2011). Materials of several of the tests from the preliminary auditory profi le are available from the HearCom website (www.hearcom.eu): Matrix sentence frameworks in the four languages, examples of words and non-words from the lexical decision-making test for the four languages, and the Gothenburg profi le questionnaire in the four languages.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This research was part of the European project HearCom (Hearing in the Communication Society, Vlaming et al, 2011). Materials of several of the tests from the preliminary auditory profi le are available from the HearCom website (www.hearcom.eu): Matrix sentence frameworks in the four languages, examples of words and non-words from the lexical decision-making test for the four languages, and the Gothenburg profi le questionnaire in the four languages.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…There has been a surge of interest in speech recognition testing in large-scale screening for clinical audiological services in the UK and Europe, Australia and the US (Meyers et al 2011; Vlaming et al 2011; Watson et al 2012). Despite this interest and an extensive body of lab-based research in speech recognition, very little population-based research has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although self-report measures have been used in parallel with previous online screening studies, like the HearCom project,9 self-reported hearing problems have not been measured in most studies. One exception is the study by Nachtegaal et al ,10 who used both data from a speech-in-noise test and questionnaires about the need for recovery after work and psychological work characteristics.…”
Section: Introductionmentioning
confidence: 99%